Actividad antifúngica del extracto etanólico de tres variedades de Solanum tuberosum L. “papa” frente a Candida albicans - Acero Rodríguez, Evelyn Solanhs (2023)
In recent decades, the frequency and importance of fungal infections has been increasing, accompanied by high mortality, which is generally caused by blood infections. The objective of this present investigation was to evaluate the in vitro antifungal effect of the ethanolic extract of three varieties of Solanum tuberosum L. against Candida albicans ATCC 24433, as well as to determine the minimum inhibitory concentration (MIC) and to compare this effect with the nystatin drug. For this purpose, the plant samples of Solanum tuberosum L. "papa" variety huayro, huaralina and tumbay were collected from different places belonging to the department of La Libertad: Huamachuco, Usquil and Julcán respectively. It was taken to the toxicology laboratory, where said samples were conditioned for the preparation of the ethanolic extract by maceration, until the dry extract was obtained. The in vitro evaluation of the antifungal activity was carried out by the microdilution method and 24 dilutions were used for each variety of Solanum tuberosum L, of which 12 were for pulp and the other half was for peel, being the concentrations of : 8192, 4096, 2048, 1024, 512, 256, 128, 64, 32, 16, 8 and 4 ug / mL. Subsequently, the seeding was carried out in 96-well microdilution plates, where 100 uL of Sabouraud-dextrose broth, 20 uL of extract and 80 uL of yeast (Candida albicans) were added, except for the control, where only the medium and the extract; and an incubator was kept for 24 hours at a temperature of 37 ° C, then 20 uL of the indicator resazurin was inoculated to all the wells of the microdilution plate; and the same initial procedure was performed with the standard drug nystatin. The dry extract of the pulp and shell of Solanum tuberosum L. variety huaralina exhibited antifungal activity against Candida albicans ATCC 24433, determining a MIC of 2048 ug / mL.